EACHERS AND STUDENTS CONCERT-CARRYING OUT ACTIVITY AT MUSIC AND PEDAGOGY FACULTIES (HISTORICAL ASPECT) - V.F. Kryvozub (Academy of Cognitive and Natural Sciences, 2007)
The article is devoted to the development of concert-carrying out activity at music and pedagogy faculties in 60s and at the beginning of 70s of the 20th century.